Music Therapy Alleviates Motor Dysfunction in Rats With Focal Cerebral Ischemia–Reperfusion Injury by Regulating BDNF Expression - Chen, Weiguan; Zheng, Jiaxuan; Shen, Guangyu; Ji, Xin; Sun, Linlin; Li, Xia; Xu, Feng; Gu, Jin-hua (Frontiers in Neurology, 2021)
Background/Aim: Music-based therapy plays a role in central nervous system diseases. We aimed to explore the effect of different doses and durations of music therapy on motor function recovery after stroke and the associated molecular mechanisms. Methods: Adult male Sprague–Dawley rats were subjected to middle cerebral artery occlusion (MCAO) for 1h, which was followed by reperfusion. Music intervention started at 1 week after surgery. Neurobehavioral dysfunction was evaluated according to modified neurological severity score, general deficits, and focal deficits. Nissl staining was performed to assess neuronal survival and regeneration. Western blot and immunofluorescence were used to detect the expression and distribution of brain-derived neurotrophic factor (BDNF) and glial fibrillary acidic protein (GFAP). Results: In the experiment of different music therapy doses, the motor function after 2 weeks music intervention in the 12-h music group but not in 1-h music group and accelerated music group (AM group) was significantly improved compared with that of the MCAO group. The BDNF protein level of the right hemisphere motor area in the 12-h music group and 1-h music group was significantly higher than that of the MCAO group. The neurons and Nissl bodies were more in the 12-h music group than in the MCAO group. Immunofluorescence assay showed that a 12-h music therapy induces BDNF and GFAP accumulation at the damage boundary. In the experiment of different music therapy durations, a 3-week continuous intervention resulted in more longer cell synapses, more clearer cell-to-cell connections, and the GFAP morphology was more similar to that of mature activated astrocytes. Moreover, the degree of cell differentiation in the music without rest group was not significantly different from that in the music with rest group. Conclusions: Music therapy could improve post-stroke dyskinesia and promote neuronal repair in the long term. The mechanism may be through stimulating BDNF and GFAP secretion in the injured motor cortex.